Effect of fracture pressures on the selection of depths for casing setting in Slovakia - Pinka, Ja; Vytyaz, O (National Mining University, 2016)
Purpose. The purpose of the article is to describe the method of casing wells for oil and gas in the Slovak Republic. Methods. Apparently there is no general method or procedure that gives the optimal location. This article is an attempt to define this optimum casing seat location. The potential benefits will improve safety and economy of the operation. The methods of predicting fracture gradients for deeper wells already exist. In this article, a method of predicting fracture gradients for shallow well has been derived. This method is combined with kick tolerance criteria to obtain a casing depth selection method. Also, the variation in fracture pressures at any depth has been investigated. Findings. The two major factors determine the depth of the casing shoe, that is, the fracture pressure and the pore pressure. A third factor is the lithology, because it is desirable to place the casing shoe in a competent shale section. Practical implications of this method is applicable in casing designing in deep hole drilling. Originality. Originality of this method lies in the fact that in this process casing wells is achieved only essential as necessary length-casing with respect to all safety and strength parameters. Practical implications. This interpretation provides the basis for vital decisions, such as selection of depths for casing setting, the maximum permissible values of mud density, method of drilling and the tightness verification of cement and cementation work. Incorrect estimates can result not only in a increase the cost of the wellbores, but also can cause potentially hazardous situations, such as lost circulation of drilling fluid, problems with managing the boreholes, borehole stability problems and also blowouts.

Мета. Метою даної статті є опис методу обсадження нафтових і газових свердловин у Словацькій Республіці. Методика. Мабуть немає загального методу або процедури, за допомогою яких можна визначати оптимальне місце розташування свердловин. Дана стаття є спробою визначити оптимальне розташування башмака обсадної колони. Потенційні вигоди дозволять підвищити безпеку та економічність експлуатації. Методи прогнозування градієнтів руйнування для більш глибоких свердловин вже існують. У статті описаний метод прогнозування градієнтів руйнування для неглибоких свердловин. Даний метод поєднується з критерієм опору породи руйнуванню, щоб отримати метод вибору глибини встановлення обсадної колони. Крім того, було досліджено зміну тисків руйнування на різних глибинах. Результати. Два основні чинники визначають глибину встановлення башмака обсадної колони, тобто тиск руйнування і поровий тиск. Третім фактором є літологія, оскільки бажано розмістити башмак обсадної колони у відповідному інтервалі сланцю. Практичне значення полягає у застосуванні цього методу при проектуванні обсадної колони в глибоких свердловинах. Наукова новизна. Унікальність даного методу полягає в тому, що в процесі обсадження свердловин важливе значення має визначення необхідної довжини обсадної труби з урахуванням всіх параметрів безпеки й міцності. Практична значимість. Дана інтерпретація є основою для прийняття важливих рішень, таких як вибір глибини встановлення обсадної колони, гранично допустимих значень густини бурового розчину, способів буріння, контролю герметичності цементування та тампонажних робіт. Неправильна оцінка може призвести не тільки до збільшення вартості спорудження свердловини, але й до потенційно небезпечних ситуацій, таких як втрата циркуляції бурового розчину, проблеми з управлінням поглиблення свердловин, проблеми стійкості стовбура свердловини, а також викиди.

Цель. Целью данной статьи является описание метода обсадки нефтяных и газовых скважин в Словацкой Республике. Методика. Пожалуй, нет общего метода или процедуры, с помощью которых можно определять оптимальное месторасположение скважин. Эта статья является попыткой определить оптимальное расположение башмака обсадной колонны. Потенциальные выгоды позволят повысить безопасность и экономичность эксплуатации. Методы прогнозирования градиентов разрушения для более глубоких скважин уже существуют. В данной статье описан метод прогнозирования градиентов разрушения для неглубоких скважин. Этот метод сочетается с критерием сопротивления породы разрушению, чтобы получить метод выбора глубины установки обсадной колонны. Кроме того, было исследовано изменение давления разрушения на разных глубинах. Результаты. Два основных фактора определяют глубину установки башмака обсадной колонны, то есть давление разрушения и поровое давление. Третьим фактором является литология, поскольку желательно разместить башмак обсадной колонны в соответствующем интервале сланца. Практическое значение состоит в применении этого метода при проектировании обсадной колонны в глубоких скважинах. Научная новизна. Уникальность данного метода заключается в том, что в процессе обсадки скважин важное значение имеет определение необходимой длины обсадной трубы с учетом всех параметров безопасности и прочности. Практическая значимость. Данная интерпретация является основой для принятия важных решений, таких как выбор глубины установки обсадной колонны, предельно допустимых значений плотности бурового раствора, способов бурения, контроля герметичности цементирования и тампонажных работ. Неправильная оценка может привести не только к увеличению стоимости строительства скважины, но и к потенциально опасным ситуациям, таким как потеря циркуляции бурового раствора, проблемы с управлением углубления скважин, проблемы устойчивости ствола скважины, а также выбросы.
Keywords: casing strings; fracture pressure; pore pressure; fracture gradients; deep hole drilling